(untitled) (Revista NUPEART, 2020)
This text, the result of academic research developed in the Graduate Program in Education (PPGEDU) of the Federal University of Mato Grosso (UFMT), brings as a central point the problem of literacy and literacy in Brazil, practices that have been the target of debates and attacks in the current Jair Bolsonaro government. The work highlights, more specifically, the relevance of the implications and reverberations of initial reading instruction unrelated to literacy. In view of the pedagogical changes brought about by the pandemic, the text also discusses the importance and challenge of playful and corporeal practices for the development of sensitive literacy and literacy, subsidized by the idea of ​​transcription, a concept presented by Almeida and Araújo (2020).